Prevalence of intimate partner violence in Malaysia and its associated factors: a systematic review - Kadir @ Shahar, Hayati; Jafri, Faridah; Mohd Zulkefli, Nor Afiah; Ahmad, Norliza (Springer, 2020)
Background: Intimate partner violence (IPV) is any behaviour within an intimate relationship that causes physical, psychological or sexual harm to those in the relationship. IPV is an important public health problem with substantial consequences on physical, mental, sexual, and reproductive health. Data on the systematic review of IPV are vital as basis for policy and program recommendations. The purpose of this systematic review was to ascertain the prevalence of IPV and its associated factors in Malaysia. Materials and methods: A systematic review was conducted on published research studies from four databases which included Scopus, Medline, Sage and Google Scholar using keywords of intimate partner violence OR IPV AND associated factors OR risk factors OR protective factors AND Malaysia. Articles included were either cross-sectional, cohort or case-control studies which were published between the year 2005 till present. Excluded articles were the non-Malaysian origin, irrelevant topics being studied and articles not written in English. Results and discussion: Out of 1983 records identified and screened, five were included for the analysis and interpretation of the data. All of the included studies were of cross-sectional design in which one of the studies was secondary data. IPV prevalence in Malaysia has a wide range between 4.94 and 35.9%. Two studies reported emotional or psychological abuse as the most common form of IPV (13% out of 22%) and (29.8%; CI = [0.27, 0.32]). Significant factors associated with IPV were lower education background, lower socio-economic status, history/ current substance abuse, exposure to prior abuse or violence, violence-condoning attitude; husbands or partners controlling behaviour, substance abuse and involvement in fights and lack of social support. Conclusion: Specific IPV intervention should focus on lower socio-economic groups, high-risk institutionalised groups, the involvement of partners or husband and addressing issues of substance abuse.